Modul siacana: Pengembangan Modul Ajar Berbasis Kurikulum Merdeka Kesiapsigaan Bencana Pada Anak Usia Dini - Fitriana (Jambura Early Childhood Education Journal, 2026)
This study aims to determine the understanding of flood disaster preparedness in early childhood, because the understanding of disaster preparedness for early childhood in Indonesia is still very low. The lack of providing knowledge of disaster preparedness, especially flood disasters in children, is caused by ineffective learning practices, because teachers have not used diverse learning media. So this research designs a computer-based educational game application product, namely learning media that displays simulations of flood disaster preparedness. Research was conducted to design learning media for understanding flood disaster preparedness in children aged 5-6 years. This research method uses research and development with the ADDIE model design (Analize, Design, Development, Implementation, Evaluate). Data collection techniques in the form of expert validation (PAUD, Media, Language, and Disaster Preparedness Experts) field trial data. The research was conducted in Group B kindergarten in Lebak Regency. The results showed that the SIGANA Banjir educational game is suitable for use to provide an understanding of flood disaster preparedness in children. Materials for understanding flood disaster preparedness in this game include: understanding hazards and early warning systems; understanding of taking action to protect oneself; understanding of reducing the impact of disasters.